Real-world patient characteristics, treatment patterns, and clinical outcomes associated with tucatinib therapy in HER2-positive metastatic breast cancer - Kaufman, Peter A.; Neuberger, Edward; Schwartz, Naomi R. M.; Wang, Shu; Liu, Yutong; Hsu, Ling-I; Bartley, Karen; Blahna, Matthew T.; Pittner, Brian T.; Wong, Gabriel; Anders, Carey (Frontiers in Oncology, 2023)
Background: Tucatinib is an oral human epidermal growth factor receptor 2 (HER2)directed therapy approved in combination with trastuzumab and capecitabine for use in patients with previously treated HER2+ metastatic breast cancer (MBC) with/without brain metastases (BM). To inform clinical decision-making, it is important to understand tucatinib use in real-world clinical practice. We describe patient characteristics, treatment patterns, and clinical outcomes for tucatinib treatment in the real-world setting.Methods: This retrospective cohort study included patients diagnosed with HER2+ MBC (January 2017-December 2022) who received tucatinib treatment in a nationwide, deidentified electronic health record-derived metastatic breast cancer database. Patient demographics and clinical characteristics were described at baseline (prior to tucatinib initiation). Key outcomes included real-world time to treatment discontinuation (rwTTD), time to next treatment (rwTTNT), and overall survival (rwOS).Results: Of 3,449 patients with HER2+ MBC, 216 received tucatinib treatment (n=153 with BM; n=63 without BM) and met inclusion criteria. Median (range) age of patients was 56 (28-84) years, 57.9% were White, and 68.5% had Eastern Cooperative Oncology Group performance status ≤1. Median (IQR) follow-up from start of tucatinib treatment was 12 (6-18) months. Among all patients who received tucatinib treatment, median (95% CI) rwTTD was 6.5 (5.4-8.8) months with 39.8% and 21.4% remaining on treatment at 12 and 24 months, respectively. Median (95% CI) rwTTNT was 8.7 (6.8-10.7) months. Patients who received the approved tucatinib triplet combination after ≥1 HER2-directed regimen in the metastatic setting had a similar median (95% CI) rwTTD (any line: 8.1 [5.7-9.5] months; second-line (2L) and third-line (3L): 9.4 [6.3-14.1] months) and rwTTNT (any line: 8.8 [7.1-11.8] months; 2L and 3L: 9.8 [6.8-14.1] months) to the overall population. Overall, median (95% CI) rwOS was 26.6 (20.2-not reached [NR]) months, with similar findings for patients who received the tucatinib triplet (26.1 [18.8-NR] months) and was NR in the subgroup limited to the 2L/3L population.Tucatinib treatment in the real-world setting was associated with a similar median rwTTD, rwTTNT, and rwOS as in the pivotal HER2CLIMB trial, with particular effectiveness in patients in the 2L/3L setting. These results highlight the importance of earlier use of tucatinib in HER2+ MBC.